Achieving universal health coverage in France: policy reforms and the challenge of inequalities. Issue 10034 (28th May 2016) - Nay, Olivier; Béjean, Sophie; Benamouzig, Daniel; Bergeron, Henri; Castel, Patrick; Ventelou, Bruno
Summary: Since 1945, the provision of health care in France has been grounded in a social conception promoting universalism and equality. The French health-care system is based on compulsory social insurance funded by social contributions, co-administered by workers' and employers' organisations under State control and driven by highly redistributive financial transfers. This system is described frequently as the French model. In this paper, the first in The Lancet 's Series on France, we challenge conventional wisdom about health care in France. First, we focus on policy and institutional transformations that have affected deeply the governance of health care over past decades. We argue that the health system rests on a diversity of institutions, policy mechanisms, and health actors, while its governance has been marked by the reinforcement of national regulation under the aegis of the State. Second, we suggest the redistributive mechanisms of the health insurance system are impeded by social inequalities in health, which remain major hindrances to achieving objectives of justice and solidarity associated with the conception of health care in France.